Analisis Penerapan Mata Pelajaran Informatika dalam Implementasi Kurikulum Merdeka Tingkat SMP - Bunga Nabilah; Supratman Zakir; Eny Murtiyastuti; Ramadhanu Istahara Mubaraq (CV Putra Publisher, 2022)
Education is very important for the continuity of human life, therefore humans should study science along with the process of growth and development. Education brings many positive changes to life if humans are good at digging and processing them well. The more advanced the times, the education also influences both formal and non-formal education. In formal education, especially at the junior high school level, children's development can be influenced by the times, therefore the child's learning process at school must continue to be supported in accordance with the times. The application of Informatics subjects can affect children's knowledge of technology which is continuously developing, in this case of course the application of Informatics subjects is important in the implementation of the current Merdeka curriculum. The lack of knowledge of students in technology along with the advancement of the times has become a problem that must be considered in the world of education. Informatics is one of the lessons that is an important component, especially in the world of teenagers or junior high school students. The purpose of this study is to analyze the application of informatics subjects in the implementation of the Merdeka curriculum. The research design uses descriptive qualitative research which is directed at analyzing the application of informatics subjects in SMP (Penggerak Schools) which lead to the implementation of Merdeka curriculum. The research results obtained are the application of Informatics subjects which have been made compulsory subjects at the junior high school level. The application of the Informatics subject was again made a compulsory subject after the implementation of the new curriculum, namely the Merdeka curriculum. This is considered with the continuity of the material in the Informatics subject with the implementation of Merdeka curriculum.